2024
DOI: 10.3390/metabo14030147
|View full text |Cite
|
Sign up to set email alerts
|

Automated Spectrophotometric Assays for the Measurement of Ammonia and Bicarbonate in Saliva of Horses: Analytical Validation and Changes in Equine Gastric Ulcer Syndrome (EGUS)

Alberto Muñoz-Prieto,
Eva Llamas-Amor,
María Dolores Contreras-Aguilar
et al.

Abstract: Ammonia (NH3) and bicarbonate (HCO3) have been related to gastric ulcers in humans. Ammonia is considered a possible cause of gastric ulcers, whereas bicarbonate has a protective function. The presence of ulcers in the stomach of horses is defined as Equine Gastric Ulcer Syndrome (EGUS), which is a frequent disease in this species, and it has been associated with changes in saliva composition, such as in analytes related to inflammation, immune system and oxidative stress. The objectives of this study were (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Based on this data, the assays could be used for the measurements of Cystatin C, ammonia, and bicarbonate in the saliva of pigs. To our knowledge, this is the first report of a specific assay for the measurement of cystatin C in the saliva of any animal species, and in the case of ammonia and bicarbonate, the validation results of this study were similar to those obtained in an analytical validation of these methods made in horse saliva [14]. In the case of ammonia and bicarbonate, the assays validated are spectrophotometric and, therefore, potentially could also be used in other animal species; however, for cystatin C, since it is an immunoturbidimetric assay that uses antibodies, a previous validation in the species to be used should be performed.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Based on this data, the assays could be used for the measurements of Cystatin C, ammonia, and bicarbonate in the saliva of pigs. To our knowledge, this is the first report of a specific assay for the measurement of cystatin C in the saliva of any animal species, and in the case of ammonia and bicarbonate, the validation results of this study were similar to those obtained in an analytical validation of these methods made in horse saliva [14]. In the case of ammonia and bicarbonate, the assays validated are spectrophotometric and, therefore, potentially could also be used in other animal species; however, for cystatin C, since it is an immunoturbidimetric assay that uses antibodies, a previous validation in the species to be used should be performed.…”
Section: Discussionsupporting
confidence: 77%
“…The evaluation of the stability after storage indicated that the three analytes are stable for short-term storage at −80 °C, at −20 °C and even at −4 °C in the case of cystatin C. Artifactual changes in ammonia and bicarbonate have been described in horse saliva and human saliva at room temperature [ 14 , 26 ]. In accordance with this data, storage at −80 °C would be recommended for these analytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Saliva is used as a sample for the measurement of biomarkers that can be related to stress, the immune system, inflammation, redox status, and the general metabolism of individuals. In horses, it can be obtained by easy collection procedures without producing stress or pain, and in cases of EGUS, changes have been described in various biomarkers, showing even differences depending on the type of EGUS [ 21 , 22 ]. However, to the authors’ knowledge, there are no reports about trace elements in the saliva of horses.…”
Section: Introductionmentioning
confidence: 99%